2019
DOI: 10.1111/eos.12617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interface surface design on the fracture behavior of bilayered composites

Abstract: This study aimed to evaluate the effect of different interface designs on the load‐bearing capacity of bilayered composite structures (BLS). Cylindrical specimens of BLS were prepared from base composite of 3.5 mm thickness and surface composite of 1.5 mm thickness (n = 80). Two different base composites – flowable bulk‐fill (FBF) [smart dentin replacement (SDR)] and short fiber‐reinforced (FRC) (everX Posterior) – were evaluated, and conventional composite (G‐ænial Posterior) was used as the surface layer. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Most dental practitioners regularly restore RCT upper premolars with conventional fiber posts, but this approach is a matter of debate [4]. There are studies to indicate that RCT upper premolars without a fiber post show similar fracture resistance to those restored with a post [59][60][61], while other studies showed superior results when a conventional FRC post was used compared to a composite filling alone [62,63]. In our present setup, there was no difference between teeth restored with a conventional composite filling alone (Group A3) or with a conventional FRC post and flowable SFRC (Group C4).…”
Section: Discussionmentioning
confidence: 99%
“…Most dental practitioners regularly restore RCT upper premolars with conventional fiber posts, but this approach is a matter of debate [4]. There are studies to indicate that RCT upper premolars without a fiber post show similar fracture resistance to those restored with a post [59][60][61], while other studies showed superior results when a conventional FRC post was used compared to a composite filling alone [62,63]. In our present setup, there was no difference between teeth restored with a conventional composite filling alone (Group A3) or with a conventional FRC post and flowable SFRC (Group C4).…”
Section: Discussionmentioning
confidence: 99%